Caracterização química das frações de N-metil-pirrolidona de asfaltenos por espectrometria de massas de Ressonância Ciclotrônica de Íons com Transformada de Fourier - Carvalho, Verônica Vale (2016)
Heavy oil fractions studies are of great importance for the oil industry, receiving special attention in recent decades due to the interest to meet them in order to obtain compounds with higher added value derived from this. Moreover, these studies also aim solutions to the problems caused by these fractions during all processing steps oil. Asphaltenes in NMP produces two fractions, a soluble and the other insoluble in NMP. It was suggested that the NI fraction present low content of aromatic compounds, opening a new debate on the composition of asphaltenes which are widely discussed in the literature as aromatic and polar compounds. In the present work is the chemical study of these asphaltenes fractions by mass spectrometry of high resolution mass and accuracy, making use of the resonance cyclotron Ion Fourier Transform (FT-ICR MS) associated with the source of atmospheric pressure ionization - ESI (electrospray ionization), infrared, fluorescence and 1H NMR. The infrared analysis, 1H NMR and Fluorescence made it possible to observe differences among samples, where NS fraction had higher amounts of heteroatoms present and a higher percentage of aromatic hydrogens and NI fraction is nonpolar in the presence of increasing amounts of alkyl and naphthenic hydrocarbons. The results of FT-ICR MS corroborated with the other results, showing that the NS fractions showed high proportion of heteroatomics species and higher DBE values compared NI fractions exhibited predominantly hydrocarbon compounds and derisory amounts of heteroatoms and also insignificant quantities compounds of DBE values different from zero.